Current Pathology, Pharmacotherapy insights and the method of awareness for effective management of Cervical Cancer (International Journal of Pharmaceutical Sciences and Drug Research, 2025)
The primary motto of the review is to analyze the current pathology and pharmacotherapy of cervical tumor; in addition to that we focus on creating awareness for early detection and vaccination to diminish the incidence of disease and death in developing countries. Cervical tumor occupied a second place among the malignance in women with primary contributor to morbidity and mortality. Approximately 500,000 females are detected with cervical tumors annually, leading to 300,000 fatalities globally. The disease is largely preventable. HPV types 16 and 18 are the primary etiological agents of cervical tumor. Accurate and early detection of abnormal cytologic changes prevents the progression of the disease. Standard treatment involves either radical surgery or radiotherapy. Childbearing is therefore impossible after the treatments.  The intensity-modulated radiotherapy, one of the advance radiotherapy technology aids reduced medication effects for women with locally advanced diseases. Cervical dysplastic lesions are prevented in eligible women who have not previously contracted the vaccine-specific HPV strains by receiving an HPV vaccination. Treatment decisions are primarily based on the stage determined by clinical FIGO staging. In wealthier nations, the utilize of pap smears has substantially decreased the occurrence of cervical tumor in low- and middle-income nations without examination and HPV vaccination programs. Approximately 90% of cervical cancer occurrences arise. Additionally, it emphasizes how important it is to prioritize efforts, especially in low- and middle-income nations. Its main goal is to raise awareness among women to lower the incidence of cervical tumor.